What Determines the DPRK's Anthracite Exports to China? Implications for the DPRK's Economy - Jong Kyu Lee (KDI Journal of Economic Policy, 2015)
Anthracite exports have special value within the DPRK's economy. In this paper, we focus on what determines the DPRK's anthracite exports to China. We use panel data consisting of cross-section data from 30 provinces in China and quarterly time-series data from 1998 to 2013. Controlling for all other variables that affect anthracite imports, the variable for steel production in China is robust and statistically significant. This is consistent with on-site interviews which indicate that much of North Korean anthracite is consumed by China's steel industry. This implies that the North Korean authorities need to make adjustments to the foreign trade structure, as the import demand for anthracite in China may decline further.
Keywords: F1; F51; 330; DPRK Economy; Export; Economic Sanction